Підприємницький клімат - Сакаї Масако (Народна творчість та етнографія, 2009)
The historical preconditions of the origin of the corporate culture in Japan are covered in the article. The peculiarities of labour legislation of the modern Japan consist in prohibition against combining jobs. It is considered that such rule supports labour discipline in the enterprises and establishments. Author, basing on the experience of other countries, insists 0n the necessity of abolition of such prohibition.